Marketsheds - HarvestChoice; Guo, Zhe; Comanescu, Maria (International Food Policy Research Institute, 2014)
This tool allows users to explore the mosaic of marketsheds that blanket sub-Saharan Africa. A market is defined as the nearest city or ‘market’ with a population greater than 20,000, 50,000, 100,000, 250,000, or 500,000. The market shed is the total area surrounding each market for which that market has the lowest cost in terms of travel time. After launching the tool, click on one of the buttons above the map to print, share, change the basemap, or create a new map by selecting a different ‘layer’ or market size. To view details about individual marketsheds, click on the map attributes.